Links between the unfolded protein response and the DNA damage response in hypoxia: a systematic review - Bolland, H; Ma, T; Ramlee, S; Ramadan, K; Hammond, E (Portland Press, 2021)
Hypoxia is a feature of most solid tumours and predicts for poor prognosis. In radiobiological hypoxia (<0.1% O2) cells become up to three times more resistant to radiation. The biological response to radiobiological hypoxia is one of few physiologically relevant stresses that activates both the unfolded protein and DNA damage responses (UPR and DDR). Links between these pathways have been identified in studies carried out in normoxia. Based in part on these previous studies and recent work from our laboratory, we hypothesised that the biological response to hypoxia likely includes overlap between the DDR and UPR. While inhibition of the DDR is a recognised strategy for improving radiation response, the possibility of achieving this through targeting the UPR has not been realised. We carried out a systematic review to identify links between the DDR and UPR, in human cell lines exposed to <2% O2. Following PRISMA guidance, literature from January 2010 to October 2020 were retrieved via Ovid MEDLINE and evaluated. A total of 202 studies were included. LAMP3, ULK1, TRIB3, CHOP, NOXA, NORAD, SIAH1/2, DYRK2, HIPK2, CREB, NUPR1, JMJD2B, NRF2, GSK-3B, GADD45a, GADD45b, STAU1, C-SRC, HK2, CAV1, CypB, CLU, IGFBP-3 and SP1 were highlighted as potential links between the hypoxic DDR and UPR. Overall, we identified very few studies which demonstrate a molecular link between the DDR and UPR in hypoxia, however, it is clear that many of the molecules highlighted warrant further investigation under radiobiological hypoxia as these may include novel therapeutic targets to improve radiotherapy response.